Application of chitosan/iota-carrageenan polymer electrolytes in electrical double layer capacitor (EDLC) - Kufian, M.Z.; Majid, Siti Rohana; Arof, Abdul Kariem; Shuhaimi, N.E.A.; Alias, N.A. (Springer Verlag (Germany), 2010)
In this work, a chitosan/iota (iota)-carrageenan blended film doped with orthophosphoric acid (H(3)PO(4)) as ionic dopant and poly(ethylene glycol) (PEG) as plasticizer has been used as a separator and electrolyte in an electrical double layer capacitor (EDLC). A set of samples were prepared by the solution cast technique to see the effect of the different weight ratios of the proton donor and plasticizer on the conductivity. The highest conducting sample has composition 37.50 wt.% chitosan-37.50 wt.% iota-carrageenan-18.75 wt.% H(3)PO(4)-6.25 wt.% PEG. The conductivity value is 6.29 x 10(-4) S cm(-1). The conductivity-temperature relationship is Arrhenian, and the activation energy for the highest conducting sample is 0.09 eV. The specific discharge capacitance of the EDLC is 35 F g(-1) at 0.11 mA cm(-2) current drain and was constant for 30 cycles.